O1-S07.05 Rare event: rectal specimen collection from males for chlamydial infection in the USA. (10th July 2011) - Tao, G; Hoover, K; Body, B; Nye, M; Kent, C
Abstract : Background: US guidelines recommend annual Chlamydia screening of the rectum and urethra among men who have sex with men (MSM) with sexual exposure at these anatomic sites. Routine pharyngeal chlamydia screening is not recommended. About 6% of US males have a history of sex with men. The prevalence of rectal chlamydia has consistently been high among MSM with a history of receptive anal sex. One study indicated that up to 53% of chlamydial infections would be missed and not treated if only urethral testing was performed among MSM. We examined data from a large commercial laboratory corporation with a substantial share of the US market and testing available across all 50 states, that also offers rectal and pharyngeal testing with nucleic acid amplification tests (NAAT), to estimate the frequency and positivity of specimens collected from men by anatomic site for chlamydia testing. Methods: Data for all Chlamydia testing methods was obtained by a large commercial laboratory between June 2008 and July 2010. The data set was then queried to obtain testing performed on males and analysed for anatomic site, test type, test result and age. Urethral and urine specimens were assumed to be testing for urethral infections. Results: Chlamydia testing was performed on 227 188 specimens from men: 98.2% urethral, 1.3% rectal, and 0.5% pharyngeal. The age distribution of those tested was: 2.4%<15 years, 15.0% 15–19 years, 15.7% 20–24 years, 15.6% 25–29 years, 12.5% 30–34 years, 10.8% 35–39 years, 10.0% 40–44 years, and 18.0% >44 years. Chlamydia positivity varied by anatomic site (8.7% rectal, 6.9% urethral, and 3.5% pharyngeal), and by age (2.5% <15 years, 13.2% 15–19 years, 12.5% 20–24 years, 7.7% 25–29 years, 5.3% 30–34 years, 3.9% 35–39 years, 3.1% 40–44 years, and 1.7% >44 years). Of 2918 rectal specimens, 17.8% were tested by culture and 75.5% by NAAT, compared to 93.5% of urethral specimens tested by NAAT. Conclusions: Given the sexual practices of men in the US, it appears that only a small proportion of MSM are appropriately screened for rectal Chlamydia. Lack of FDA clearance for these specimen sources may contribute to the small proportion of MSM being screened for rectal Chlamydia. Interventions to increase rectal chlamydial testing among MSM are needed. Because data from this corporation represents a large proportion of testing in the US, it could be used to monitor changes in chlamydia testing practice among men in the future.